Peralihan Izin Mendirikan Bangunan Menjadi Persetujuan Bangunan Gedung Berdasarkan Undang-Undang Nomor 11 Tahun 2020 Tentang Cipta Kerja - Roman Situngkir (Iuris Studia: Jurnal Kajian Hukum, 2021)
Based on Law Number 28 of 2002 concerning Buildings and Government Regulation Number 36 of 2005 concerning Implementing Regulations of Law Number 28 of 2002 concerning Buildings, it is explicitly stated that a building permit is a permit granted by the Regency/Municipal Government. City to building owners to build new, modify, expand, reduce and/or maintain buildings in accordance with applicable administrative and technical requirements, while Government Regulation Number 16 of 2021 concerning Implementing Regulations of Law Number 28 of 2002 concerning Buildings . Article 1 number 17 states that Building Approval, hereinafter abbreviated as PBG, is a permit granted to a building owner to construct a new building, modify, expand, reduce and/or maintain a building in accordance with the technical standards of the building. This research is a normative legal research, so according to the type and nature of the research, the data sources used are secondary data consisting of primary legal materials and secondary legal materials consisting of books, scientific journals, scientific works, and articles that can provide explanations about the law. primary material. The nature of this research is descriptive analytical. As for what is meant by descriptive analytical research is a research that can describe in detail and systematically about the object under study. Primary legal materials are legal materials that bind or make the public understandable, including legal products that are the subject of study and legal products as tools for forming critical law. Secondary legal materials include explanations of primary legal materials in the form of expert doctrine found in books, journals, and websites. The results showed that every building has a function and classification of buildings, the function of the building must be used in accordance with the location designation stipulated in the RDTR and the function of the building included in the Building Approval. The construction of buildings is carried out through the stages of planning, implementation and supervision. Construction is carried out after obtaining Building Approval. Building approval is obtained after obtaining a statement on the fulfillment of building technical standards from the Regional Government in accordance with its authority